Passive Voice and Active Voice in Sentence Structure - M. Yusri Ali Lubis; Reysha Miranti; Yani Lubis (Journal Of Psychology, Counseling And Education, 2024)
Background: Expert guidelines recommend using active over passive voice to improve clarity in English academic writing. However, few systematic reviews synthesize research on reader outcomes from texts written in the passive versus active voice. This paper reviewed experimental studies comparing the effects of active and passive voice on reader comprehension in English academic writing. Methods: Following PRISMA guidelines, database searches identified quantitative studies manipulating voice in academic texts and measuring differential impacts on reader understanding. 9 eligible studies were analyzed narratively. Results: Studies consistently demonstrated reduced readability, slower processing, and lower comprehension scores for passive versus active voice texts across reader groups and disciplines. On coherence ratings, grammatical errors, and comprehension questions, passive voice performed significantly worse. Conclusions: Strong evidence confirms active voice improves reader comprehension over passive in academic writing. However, strategic passive usage may still benefit writing on a situational basis. More research is needed on providing effective instruction to EFL students on selectively deploying active/passive principles. Originality: This systematic review is the first to synthesize major studies comparing active and passive voice impacts on reader outcomes in academic writing. The consistent experimental results provide an empirical basis for style guidelines favoring active voice for clarity.